2019
DOI: 10.1109/tbme.2018.2845689
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect of Low-Intensity Transcranial Ultrasound Stimulation

Abstract: TUS has been speculated to have therapeutic effect in depression. This study provide evidence for the antidepressant-like effects of TUS in rats for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…LIPUS provides a promising new approach for the noninvasive modulation of brain activity and has numerous potential applications in the treatment of neurologic and psychiatric disease, such as epilepsy [ 26 ], stroke [ 27 ], depression [ 28 ] and disorders of consciousness [ 29 ]. In our study, we found that the anesthetic dose can affect the neuromodulation effect of ultrasound on the motor cortex when we used the ultrasound to stimulate different rodent disease models under anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS provides a promising new approach for the noninvasive modulation of brain activity and has numerous potential applications in the treatment of neurologic and psychiatric disease, such as epilepsy [ 26 ], stroke [ 27 ], depression [ 28 ] and disorders of consciousness [ 29 ]. In our study, we found that the anesthetic dose can affect the neuromodulation effect of ultrasound on the motor cortex when we used the ultrasound to stimulate different rodent disease models under anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 156 articles were subjected to full-text review, of which 121 articles were removed for the following reasons: review or commentary ( n = 52), study regarding the application of ultrasound in neurosurgery ( n = 7), technique papers regarding the design of ultrasound system, stimulation protocol, parameter optimization and properties improvement ( n = 39), computational modeling or simulation study ( n = 4), ultrasonic stimulation targeting peripheral or cranial nerves rather than cortical and subcortical structures ( n = 4), study with surrogate biomarkers as outcomes exclusively ( n = 14), study regarding seizure control ( n = 1) and study using mixed ultrasound magnetic stimulation ( n = 1). Ultimately 35 studies (Tufail et al, 2010; Yoo et al, 2011a,b, 2018; Deffieux et al, 2013; Hameroff et al, 2013; Kim et al, 2013, 2014a,b, 2015; Legon et al, 2014, 2018a,b; Chu et al, 2015; Guo et al, 2015, 2018; Lee et al, 2015, 2016a,b,c; Ai et al, 2016, 2018; Monti et al, 2016; Yu et al, 2016; Wattiez et al, 2017; Dallapiazza et al, 2018; Daniels et al, 2018; Gibson et al, 2018; Sato et al, 2018; Xie et al, 2018; Yang et al, 2018; Zhang et al, 2018; Li et al, 2019; Sharabi et al, 2019) were selected for inclusion in this review, including 24 animal and 11 human studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that TUS altered the cortico-muscular coupling (i.e., coupling relationship between stimulated motor cortex and effector muscle), which was significantly enhanced with the increase of the number of tone bursts applied (Xie et al, 2018). Experimental rats with diseases conditions were used in three articles: the first reported that 360 trials (400 ms per trial) ultrasonic stimulation over the ischemic core at an intensity of = 2.155 W/cm 2 (spatial peak pulse average intensity, ISPPA) significantly reduced the volume of lesion and improved the neurological outcomes in stroke rats, as comparison to the sham stimulation (Guo et al, 2015), the second showed that prefrontal 2-week ultrasonic stimulation at an intensity of 7.59 W/cm 2 (ISPPA) improved the depression-like behaviors of depressed rats (Zhang et al, 2018) and the third reported that TUS at an intensity of 27.2 W/cm 2 (ISPPA) over the medulla oblongata region could suppress the essential tremors (Sharabi et al, 2019) in Harmaline-induced rats.…”
Section: Resultsmentioning
confidence: 99%
“…LIPUS stimulation of olive-cerebellar pathways decreases tremor frequency in a rat model of essential tremor [27]. Seizure activity in the animal model of epilepsy is also suppressed by the LIPUS treatment [2830] and depressive symptoms are reversed by LIPUS stimulation of the prelimbic cortex [31]. Furthermore, LIPUS stimulation of the ischemic cortex mitigates focal cerebral ischemia in a rat model of stroke induced by distal middle cerebral artery occlusion [24, 32].…”
Section: Introductionmentioning
confidence: 99%